KONTRIBUSI PDRB SUBSEKTOR PERIKANAN TERHADAP PERTUMBUAN EKONOMI KABUPATEN ACEH TIMUR - Fitrah Maulana Batubara; Zulkifli Zulkifli (Jurnal Ilmiah Mahasiswa Ekonomi Pembangunan, 2019)
Abstract This study examines the contribution of the fisheries sub-sector to the Gross Regional Domestic Product (GRDP) in East Aceh region. The objective of this research is to identify the contribution of GRDP of fisheries subsector to economic growth in East Aceh region. The methodology used in this study is a quantitative descriptive model with time series data from 2012-2016. This research was conducted in East Aceh region. The result reveals that contribution of the fisheries subsector to the Gross Regional Domestic Product in East Aceh region is decreasing significantly from 2012 to 2016. The average of fisheries sub-sector contribution to GRDP is approximately 11.87 %. However, fisheries sub-sector is accounted as a sector that has the highest contribution by 24.58 % to GRDP in East Aceh region compared to other Agricultural sub-sectors. Keywords :Fisheries, GRDP, Economic Growth